(untitled) (Al-Qamar, 2018)
In the nineteenth century religious traditional system of learning was popular among Muslims. In such system there were fewer educational opportunities for Muslim girls. The only opportunity for Muslim girls was in the form of Maktabs to learn recitation of the Holy Quran in their childhood. After Maktab education there was no space of formal education of the Muslim girls. Even in the mid of nineteenth century the Muslim girls who belonged to Muslim elite class were taught to read the Holy Quran and little bit grammar. In some Muslim elite families girls were allowed to learn Arabic, Persian and Urdu languages but only at home from their father and brothers. Inevitably; one must come forward to mobilize people in favor of modern education for male as well as for female to safeguard purity of Muslim civilization and Muslim identity in emerging political paradigm of colonial India. Such rigidity was more intensive in colonial Punjab. In non-favorable circumstance for Muslim women education in colonial Punjab the efforts of Mawlānā Abdul Ḥaq Abbās (1884-1960) were remarkable and the role of Madrasa al-Banāt was undeniable.